Peculiarities of the crystal packing of n-alkyl side chain ureas—precursors in the synthesis of helical polycarbodiimides. Issue 46 (18th November 2015) - Kulikov, Oleg V.; McCandless, Gregory T.; Siriwardane, Dumindika A.; Sevryugina, Yulia V.; Novak, Bruce M.
Graphical abstract: Abstract: We report here the single-crystal X-ray diffraction data collected for 10 ureas bearing alkyl side chains—precursors in the synthesis of chiral polycarbodiimides. X-ray data obtained could be used in constructing the model of interacting polymer chains (e.g., n -hexyl, n -heptyl, n -octyl, n -nonafluoropentyl, and n -heptadecafluorononyl). TGA/DSC studies confirmed relative stability of the ureas inspected. It seems probable that interdigitation pattern found in a crystal lattice of the aliphatic ureas mimics the organization of polycarbodiimide macromolecules identifiable by microscopy techniques